Transversal Vortex-Induced Vibration of a Circular Cylinder in Tandem with a Stationary Square Structure - Henry Francis Annapeh; Victoria Kurushina (Applied Mechanics)
This paper considers a system with two offshore structures in tandem, where the upstream square structure is fixed and the downstream circular structure has one degree of freedom. Cylinders are subject to uniform and linearly sheared flow conditions. The dynamics of the downstream structure are investigated by using a computational fluid dynamics approach for a Reynolds number range of 1000–6500 at the centerline. The spacing ratio for the tandem structures is L/D = 6 in this work, corresponding to the wake interference regime. The effect of the shear parameter on the development of vortex-induced vibrations in the lock-in state within the downstream structure is studied, in comparison with the lock-in of an isolated circular structure. The results of this research include statistics on the displacement amplitude, drag and lift coefficients, frequency ratio, time histories and contours of vorticity. The results obtained show the maximum displacement amplitude of the isolated structure in a uniform flow at the level of 0.8 diameters during the upper branch. The investigation also shows a later development in the maximum displacement during the upper branch of the downstream structure under shear flow conditions, with the highest maximum displacement of 1.18 diameters seen for the shear parameter of 0.05.